Selecting and optimising patients for total knee arthroplasty. Issue 3 (18th January 2019) - Adie, Sam; Harris, Ian; Chuan, Alwin; Lewis, Peter; Naylor, Justine M
Summary: The minimum requirements for total knee arthroplasty (TKA) are significant, prolonged symptoms with supporting clinical and radiological signs. Despite interest in screening tools, there is limited evidence for a specific symptom threshold that justifies surgery. Non‐operative treatments including medications, exercise and weight loss are unlikely to reverse radiographic changes, but they may improve symptoms and delay the need for surgery. Many patient factors such as mental health and obesity affect both the level of symptomatic improvement after surgery and risks of surgery, but none have been identified as contraindications for the procedure as significant health gains can still be achieved. Although age and sex are associated with patient‐reported outcomes and risk of revision, these factors cannot be used to restrict access to TKA, and age cut‐offs are not recommended. Evidence regarding pre‐operative optimisation of patients to improve post‐operative TKA outcomes is limited by the few interventional trials available, particularly in the areas of patient expectation, diabetes, obesity and vascular disease. There is good evidence from randomised controlled trials that pre‐operative rehabilitation primarily focusing on exercises for the joint or limb has minimal effect on post‐operative TKA outcomes, and there is some evidence from randomised controlled trials that an intensive smoking cessation program before surgery may improve post‐operative outcomes. Detailed international guidelines exist on the optimisation of the cardiorespiratory status of surgical patients, and these should be followed for TKA surgery.